2008
DOI: 10.1099/vir.0.2008/006254-0
|View full text |Cite
|
Sign up to set email alerts
|

The human H5N1 influenza A virus polymerase complex is active in vitro over a broad range of temperatures, in contrast to the WSN complex, and this property can be attributed to the PB2 subunit

Abstract: Influenza A virus (IAV) replicates in the upper respiratory tract of humans at 33 °C and in the intestinal tract of birds at close to 41 °C. The viral RNA polymerase complex comprises three subunits (PA, PB1 and PB2) and plays an important role in host adaptation. We therefore developed an in vitro system to examine the temperature sensitivity of IAV RNA polymerase complexes from different origins. Complexes were prepared from human lung epithelial cells (A549) using a novel adenoviral expression system. Affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…We next determined the contribution of Cal PA to polymerase activity in human lung epithelial A549 cells, which are more closely related to the natural site of infection. Because of low transfection efficiency, we used adenovirus-mediated transduction of A549 cells as we reported previously (1). Similar to our results in 293T cells, the Cal complex was highly active in A549 cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…We next determined the contribution of Cal PA to polymerase activity in human lung epithelial A549 cells, which are more closely related to the natural site of infection. Because of low transfection efficiency, we used adenovirus-mediated transduction of A549 cells as we reported previously (1). Similar to our results in 293T cells, the Cal complex was highly active in A549 cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…BradelTretheway et al showed that the avian VN04 polymerase complex is transcriptionally active up to 42°C, whereas the human WSN polymerase complex lost activity at 39°C or higher. Through reassortant RNP molecules, they discovered that this activity is attributable to the PB2 gene (17). Kashiwagi et al also used VN04 and WSN reassortant RNP complexes, but they showed that thermal sensitivity is dependent on the species of origin of the PA gene (18).…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, we purified the H5N1 (Vietnam/1203/04 [VN/1203]) polymerase (3P) complex and its subunit components (PA and PA-PB1) from human lung epithelial cells (A549 cell line) infected with adenovirus (Ad) vectors encoding these proteins. This novel expression system allows for the expression and purification of high levels of polymerase proteins (2). We analyzed proteins in the purified fractions by mass spectrometry, either before or after nuclease treatment to remove copurified RNA (and to dissociate protein complexes held together through an RNA intermediate).…”
mentioning
confidence: 99%
“…The polymerase genes from the H1N1 virus of a recent pandemic (CA/04/09) were human codon optimized and assembled from synthetic oligonucleotides by EpochBiolabs (Missouri City, TX); protein identifiers (IDs) for polymerase genes of CA/04 were ACP44156.1, ACP41103.1, and ACP41102.1. The adenoviral vectors were constructed as described previously (2). Briefly, PA from each viral strain was tagged at the C terminus with a tandem affinity purification (TAP) tag, and the viral polymerase genes were cloned into adenoviral expression vectors as described for A/Vietnam/1203/04.…”
mentioning
confidence: 99%
See 1 more Smart Citation